If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 2Y = 7 Reorder the terms: 2Y + y = 7 Solving 2Y + y = 7 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-1y' to each side of the equation. 2Y + y + -1y = 7 + -1y Combine like terms: y + -1y = 0 2Y + 0 = 7 + -1y 2Y = 7 + -1y Divide each side by '2'. Y = 3.5 + -0.5y Simplifying Y = 3.5 + -0.5y
| x+7.8=14.3 | | 10x+23(x-3)=162 | | 4-4=10y+3-9y | | 0.9x-1.9y=1.43 | | x+2y=1.5 | | 15+8x-3x^2=0 | | 14m+7n-2mn+n= | | -4+-2+x=180 | | 20z+1=24z+7 | | -7-5x+4=-24x+18-5x | | (2x+10)+(x-10)+(2x-20)=180 | | (9x+24)=(6+66) | | -4x^2=8x-3 | | (X+30)+(2x)+(3x-30)=180 | | 12x-11x-2=-4 | | 2x^3-6x^2+4x-12=0 | | 7(x+7)=30 | | 6y=3.5 | | (2x)+(x+10)+(3x-10)=180 | | -9+2=-16 | | 5(x+4)+5=1 | | -3x-1.5y=0 | | 8y-12=6+2(10y-3) | | 2/3=k/9 | | 4/3=24/r | | 4/3=23/r | | 4x^2+8=10 | | -2(x+2)-4(x-3)=22 | | X+86+35+63+x=180 | | (2x)+(x+10)+(3x-7)=180 | | 3x=3.84 | | -5t-4(2+2t)=-4 |